2010
DOI: 10.1007/978-3-642-16822-2_7
|View full text |Cite
|
Sign up to set email alerts
|

On the Claimed Privacy of EC-RAC III

Abstract: In this paper we show how to break the most recent version of EC-RAC with respect to privacy. We show that both the ID-Transfer and ID&PWD-Transfer schemes from EC-RAC do not provide the claimed privacy levels by using a man-in-the-middle attack. The existence of these attacks voids the presented privacy proofs for EC-RAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The authors claimed that by nonlinearity EC-RAC III is able to be resistant to the attacks in [9]. The protocol, unlike the author's claim, is still not secure against the man-in-the-middle attacks on traceability, as shown by Fan, Hermans and Vercauteren in [12]. A…”
Section: Related Workmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors claimed that by nonlinearity EC-RAC III is able to be resistant to the attacks in [9]. The protocol, unlike the author's claim, is still not secure against the man-in-the-middle attacks on traceability, as shown by Fan, Hermans and Vercauteren in [12]. A…”
Section: Related Workmentioning
confidence: 90%
“…For EC-RAC III, it does not satisfy both privacy properties, untraceability and forward privacy, as demonstrated in [12]. For EMA, reduced PII and SPA, they do not support even the property of impersonation resistance that is one of the core security requirements any authentication scheme must satisfy.…”
Section: Advantagesmentioning
confidence: 93%
“…EC-RAC has been gradually revised in [19,17]. However, Fan et al [10] have shown that the most recent version of EC-RAC [17] is not wide-weak privacy preserving.…”
Section: State Of the Artmentioning
confidence: 99%
“…Finding appropriate trade-offs which meet this requirement while simultaneously catering for any resource constraints is difficult however. In common with other examples, this is 1 For an excellent overview, see [ highlighted by the EC-RAC family [27,28,26] of ECC-based protocols, each of which was broken [6,38,14].…”
Section: Introductionmentioning
confidence: 97%